1966
DOI: 10.1113/jphysiol.1966.sp007932
|View full text |Cite
|
Sign up to set email alerts
|

Observations on temperature distribution in the cardiovascular system, thorax and abdomen of monkeys in relation to environment

Abstract: SUMMARY1. Thermo-electric observations of temperature distribution in the 'core 'area of monkeys and baboons are reported.2. Temperature gradients were shown to exist in the inferior vena cava, temperatures rising by a mean value of 0.20 C at the entry of the renal veins and again by a further 0.20 C at the level of the hepatic veins.3. Temperatures in the right atrium were on average 0-10 C lower than in the inferior vena cava due to the return of relatively cooler blood from the superior vena cava.4. Net hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…The total heat production of the splanchnic area was, in fact, about one third of the total for the anaesthetized dog. This is slightly less than the estimate of Grayson et al (1966), but it should perhaps be remembered that the figures quoted here are minimal and the splanchnic heat production may well be even higher than calculated.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The total heat production of the splanchnic area was, in fact, about one third of the total for the anaesthetized dog. This is slightly less than the estimate of Grayson et al (1966), but it should perhaps be remembered that the figures quoted here are minimal and the splanchnic heat production may well be even higher than calculated.…”
Section: Discussioncontrasting
confidence: 63%
“…The present experiments show that in the dog, as in the monkey (Grayson et al 1966), temperatures in the gastro-intestinal tract are substantially higher than in the aorta, with maximum temperatures in the duodenum (0.60 C hotter than aorta). The temperature of the rectum, however, was not significantly different from that of the aorta.…”
Section: Discussionmentioning
confidence: 44%
“…Temperatures were measured thermo-electrically (Grayson, Irvine and Kinnear, 1966) from the lumen of the stomach, duodenum, ileum, large intestine and the rectum. The gastric applicator was introduced through the mouth, the intestinal applicators were inserted by direct vision, after laporotomy, through small incision penetrating the bowel and closed around the probe by pursestring sutures.…”
Section: Me Thodsmentioning
confidence: 99%
“…Later, Grayson, Irvine and Kinnear {1966) showed that the gastro-intestinal tract of monkeys, dogs and of man was a substantial producer of heat, the bowel lumen being about 0.6°C hotter than the aortic blood. The liver, in fact, had a lower total heat production and, being cooled by hepatic arterial blood was at a lower temperature.…”
mentioning
confidence: 98%
“…The work presented in this study supported the prediction that fewer genes would be expressed at higher ambient temperatures, but also lent to new speculation about the mechanism of TDT. Changes in blood flow could be partially responsible for TDT, because blood flow is known to be diverted to the periphery and away from the viscera as a thermoregulatory response in mammals at warmer temperatures (Dearing, ; Grayson, Irvine, & Kinnear, ). However, blood shunting is an immediate, physiological response to thermal stress that is often short term and potentially energetically expensive (Hales et al., ; Reichard, Prajapati, Austad, Keller, & Kunz, ).…”
Section: Discussionmentioning
confidence: 99%